Warmer Temperatures Affect the in situ Freezing Resistance of the Antarctic Vascular Plants - Sierra-Almeida, Angela; Cavieres, Lohengrin A.; Bravo, León A. (Frontiers in Plant Science, 2018)
Although positive effects on growth and reproduction of Antarctic vascular plants have been reported under warmer temperatures, it could also increase the vulnerability of these plants to freezing. Thus, we assessed in situ whether warming decreases the freezing resistance of Colobanthus quitensis and Deschampsia antarctica, and we compared the level and mechanism of freezing resistance of these species in the field with previous reports conducted in lab conditions. We assessed the freezing resistance of C. quitensis and D. antarctica by determining their low temperature damage (LT50), ice nucleation temperature (NT) and freezing point (FP) in three sites of the King George Island. Plants were exposed during two growing seasons to a passive increase in the air temperature (+W). +W increased by 1K the mean air temperatures, but had smaller effects on freezing temperatures. Leaf temperature of both species was on average 1.7K warmer inside +W. Overall, warming decreased the freezing resistance of Antarctic species. The LT50 increased on average 2K for C. quitensis and 2.8K for D. antarctica. In contrast, NT and FP decreased on average c. 1K in leaves of warmed plants of both species. Our results showed an averaged LT50 of -15.3°C for C. quitensis, and of -22.8°C for D. antarctica, with freezing tolerance as freezing resistance mechanism for both species. These results were partially consistent with previous reports, and likely explanations for such discrepancies were related with methodological differences among studies. Our work is the first study reporting the level and mechanisms of freezing resistance of Antarctic vascular plants measured in situ, and we demonstrated that although both plant species exhibited a great ability to cope with freezing temperatures during the growing season, their vulnerability to suffer freezing damage under a warming scenario increase although the magnitude of this response varied across sites and species. Hence, freezing damage should be considered when predicting changes in plant responses of C. quitensis and D. antarctica under future climate conditions of the Antarctic Peninsula.